New species of Crella (Pytheas) Topsent, 1890 and Crellomima Rezvoi, 1925 (Crellidae, Poecilosclerida, Demospongiae) from Chilean shallow and Argentinean deep waters, with a synthesis on the known phylogenetic relationships of crellid sponges - Fernandez, Julio C.c.; Gastaldi, Marianela; Zapata-Hernández, Germán; Pardo, Luis M.; Thompson, Fabiano L.; Hajdu, Eduardo (Zootaxa, 2021)
Here, we describe four new species of Crellidae Dendy, 1922 and discuss characters and relationships from published molecular phylogenies including crellid sponges. New species proposed are Crella (Pytheas) chiloensis Fernandez, Gastaldi, Pardo & Hajdu, sp. nov., from southern Chile (15 m depth), C. (P.) desventuradae Fernandez, Gastaldi, Zapata-Hernández & Hajdu, sp. nov., from Desventuradas Archipelago (10–20 m depth), Crella (P.) santacruzae Fernandez, Gastaldi, Thompson & Hajdu, sp. nov., from deep waters off Argentina (750 m depth) and Crellomima sigmatifera Fernandez, Gastaldi & Hajdu, sp. nov., from the Chilean fjords region (ca. 20 m depth). These new species are set apart from each other and from known species mainly due to aspects of their spiculation. Chelae microscleres and acanthostyles supply characters that might be used to infer phylogenetic relationships and to verify the monophyly of Crella Gray, 1867 and Crellidae, which has seemingly been contradicted by preliminary molecular data available in the systematics’ literature. Our own interpretation of phylogenetic affinities, in the light of morphological characters from previous taxonomic studies, argues for a classification reassessment of materials (vouchers) included in these molecular phylogenies, especially in the case of Crella incrustans (Carter, 1885). We argue that currently available molecular phylogenetic outcomes for crellid sponges are not supportive of the polyphyly of Crella and Crellidae.